Langasite Family Midinfrared Nonlinear Optical Oxide Materials: Structure, Property, and Applications. (5th November 2017) - Lan, Haichao; Liang, Fei; Lin, Zheshuai; Yu, Haohai; Zhang, Huaijin; Wang, Jiyang
Abstract : Midinfrared (IR) nonlinear optical (NLO) materials with high performance are vital in important technological applications in many civil and military fields. Very recently, langasite family compounds have attracted much attention due to their wide transparency to mid-IR region and ultrahigh laser damage threshold (LDT). In this brief review, three important compounds—LGS, LGN, and LGT—are investigated and analyzed based on available experimental data. The electrooptical (EO) Q-switch and mid-IR OPO applications are summarized in detail. Finally, promising search directions for new metal oxides that have good mid-IR NLO performances are discussed.